DESIGN AND CONSTRUCTION OF A MAGNETIC INDUCTION HEATING SYSTEM - ELMONTASSER BIALLAH BENGUESSOUM; SABER TOUATI; MOHAMAD BACHIR HAMMIA (University of Shahid Hama Lakhdar - El Oued, 2025)
Induction heating is a clean, efficient, and rapid method of heating electrically conductive materials using electromagnetic fields. This project presents realization, the complete design, simulation, and experimental validation of a low-voltage magnetic induction heating system based on a Zero Voltage Switching (ZVS) inverter operating at 12V. The objective was to investigate the thermal response of various steel objects when exposed to a resonant electromagnetic field generated by a custom-designed induction coil. The project included theoretical grounding in electromagnetic principles, detailed system architecture development, component selection, and implementation of safety and control mechanisms. Experimental results demonstrated successful heating of various ferromagnetic materials with controlled power input and measurable thermal efficiency. Simulations performed in MATLAB/Simulink confirmed resonance operation and high current generation, validating theoretical predictions. التسخين الحثي طريقة نظيفة، فعّالة، وسريعة لتسخين المواد الموصلة للكهرباء باستخدام المجالات الكهرومغناطيسية. يقدم هذا المشروع تصميمًا كاملاً، ومحاكاة، واختبارًا تجريبيًا لنظام تسخين حثي مغناطيسي منخفض الجهد، يعتمد على عاكس تحويل جهد صفري يعمل بجهد 12 فولت. كان الهدف دراسة الاستجابة الحرارية لمختلف الأجسام الفولاذية عند تعرضها لحقل كهرومغناطيسي رنيني ناتج عن ملف حثي مصمم خصيصًا. تضمن المشروع أسسًا نظرية لمبادئ الكهرومغناطيسية، وتطويرًا مفصلًا لبنية النظام، واختيار المكونات، وتطبيق آليات السلامة والتحكم. أظهرت النتائج التجريبية نجاح تسخين مختلف المواد المغناطيسية الحديدية باستخدام مدخلات طاقة متحكم بها وكفاءة حرارية قابلة للقياس. أكدت عمليات المحاكاة التي أُجريت في المحاكاة فعالية الرنين وتوليد تيار عالي، مما أثبت صحة التنبؤات النظرية
Master's thesis in electromechanics
Keywords: Induction heating; electromagnetic induction; MATLAB simulation; التسخين الحثي، الحث الكهرومغناطيسي، المحاكاة